5% or 30%: That is the question! Tax treatment of capital gains from the sale of shares on the Lima Stock Exchange - Núñez Ciallella, Fernando (2019)
This article aims to analyze the application of the reduced rate of 5% on capital gains obtained by non-domiciled parties from operations on the Lima Stock Exchange. From a strictly legal perspective, the application of this reduced rate is subject to the fulfillment of two specific requirements that do not merit greater doubt as to their compliance. However, a recent Tax Court ruling would seem to introduce a series of additional requirements that would affect the application of the 5% rate and that would put non-domiciled investors in a situation of uncertainty.